Knowledge and Organizational Practices of Popular Cultures in the Municipality of Caruaru, Pernambuco, Brazil - Cavalcante dos Santos, Elisabeth; de Freitas Ramos da Silva, Ítalo Henrique; Dias, Pâmela Karolina; Morais, Wilson Mike (Organizações & Sociedade, 2021)
This paper examines the embodied practical knowledge (know-how) that make up the organizational practices of popular cultures in the northeast Brazilian municipality of Caruaru, located in the microzone of Agreste in the state of Pernambuco. We held informal and semi-structured interviews with fifteen masters and artists from Caruaru, linked to eleven different popular culture segments, and performed non-participant observation in workshops, meetings, and forums. Our discussion reflects on the ancestries, affections between family members, masters and apprentices, explicit rules, conflicts, and distinctions constituting the popular know-how that underlies organizational practices. We highlight as the main contributions of this study to Organizational Studies: the production of authentic knowledge about organizing practiced in peripheral contexts; and the questioning of the distinction between ‘knowing’ and ‘doing’ and instrumental rationality as the basis for organizational practices. Finally, we point out how practice theory initiates a wider discussion about popular cultures in a peripheral context like the Agreste of Pernambuco, which includes the contribution of other perspectives and leads to concrete actions in practice.